The role of soft negotiation skills in resolving conflicts through publicrelations strategies (Eurasian Journal of Media and Communications, 2026)
This study aims to explore the relationship between soft negotiation skills and public relations strategies in managing organizational conflicts by developing a theoretical framework that demonstrates how the integration of both elements can lead to effective and peaceful resolutions. The significance of the study lies in both its theoretical and practical contributions: it seeks to bridge a knowledge gap in the Arab academic literature regarding this integration, and it offers guidance for public relations practitioners to enhance their negotiation capabilities. The study adopts a descriptive-analytical methodology based on an extensive review of relevant literature and previous studies, allowing for a critical analysis of multiple conceptual frameworks. Findings indicate that soft negotiation skills—such as persuasion, emotional intelligence, and active listening— effectively contribute to conflict mitigation, especially when combined with public relations strategies focused on institutional communication, transparency, and trustbuilding. The study recommends the development of comprehensive training programs that integrate soft skills with communication strategies, emphasizing practical simulations, the use of objective performance assessment tools, and stronger collaboration between academics and professionals to transfer these skills into realworld institutional settings. This, in turn, enhances organizational performance and reduces internal conflict intensity.